Reconstructing Class Sport Practices in Post-Communist Poland - Lenartowicz Michał; JankowskiC Krzysztof W. (Sciendo, 2014)
The article analyzes the changes in attitude of Poles towards sport and recreational activities as well as their participation in these disciplines between the period before system transformations and the present day. Based on examples from literature and own studies, we have observed that Poles have shown a growing interest in sport and recreational activities. Moreover, social diversity of participants in this field has been noted. Sport disciplines and diverse recreational activities perceived as "bourgeois" during the socialist period are becoming more popular among members of the middle and upper classes as potential attractive and clear markers of social status. Interest in sport, skills, knowledge, and sports equipment and outfit in such disciplines as sailing, horse riding, golf, and hunting are thus becoming distinctive social markers. These factors are adopted in the reconstruction of sports practiced by members of different social classes. The continuity of sport practice was abruptly interrupted by the outbreak of the Second World War and the following half-century of socialism